Solvent-free acrylic pressure-sensitive adhesive composition and pressure-sensitive adhesive sheet

The solvent-free acrylic adhesive composition, featuring a blend of acrylic copolymers and a hydrogenated petroleum resin, addresses the challenge of adhesion to low surface free energy adherends, resulting in an adhesive sheet with excellent transparency and adhesion, and aligns with environmental sustainability goals.

JP2025040937APending Publication Date: 2025-03-25SAIDEN CHEM IND

Patent Information

Application Number
JP2024105455
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Acrylic adhesives face challenges in achieving sufficient adhesion to low surface free energy adherends, such as polyolefin resins, and existing solutions using tackifying resins often result in curing inhibition and inadequate adhesive properties.

Method used

A solvent-free acrylic adhesive composition is developed, comprising a specific blend of first and second acrylic partial copolymers, a multifunctional monomer, and a hydrogenated petroleum resin as the tackifying resin, which is cured using active energy rays to form an adhesive sheet with improved transparency and adhesion.

Benefits of technology

The solvent-free acrylic adhesive composition achieves excellent transparency and sufficient adhesive properties to low polarity adherends, while being environmentally friendly and safe for human use, contributing to the UN-led Sustainable Development Goals (SDGs) Goal 12.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025040937000001
    Figure 2025040937000001
  • Figure 2025040937000002
    Figure 2025040937000002
  • Figure 2025040937000003
    Figure 2025040937000003
Patent Text Reader

Abstract

To provide a solvent-free acrylic pressure-sensitive adhesive composition realizing a pressure-sensitive adhesive sheet that exhibits excellent transparency and sufficient properties of adhesion to low-polarity adherends.SOLUTION: The composition comprises: either a first acrylic partial copolymer containing 60 to 93 pts.mass of a (meth)acrylic acid ester having an alkyl group with 8 or more carbon atoms, 0 to 30 pts.mass of a (meth)acrylic acid ester having an alkyl group with less than 8 carbon atoms, and 7 to 20 pts.mass of a monomer having a functional group, or a second acrylic partial copolymer containing 0 to 63 pts.mass of a (meth)acrylic acid ester having an alkyl group with 8 or more carbon atoms, 30 to 93 pts.mass of a (meth)acrylic acid ester having an alkyl group with less than 8 carbon atoms, and 7 to 20 pts.mass of a monomer having a functional group; a polyfunctional monomer; and a tackifier resin, which is a hydrogenated petroleum resin and is contained in an amount of 0.5 to 4.5 pts.mass based on 100 pts.mass of the second acrylic partial copolymer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solventless acrylic pressure-sensitive adhesive composition and a pressure-sensitive adhesive sheet. [Background technology]

[0002] Acrylic adhesives are used as adhesive layers provided on substrates such as various labels, sheets, tapes, and films. In recent years, solvent-free acrylic adhesives that do not use solvents and have the same performance as solvent-based acrylic adhesives have been developed in consideration of environmental and safety considerations. As a result, UV-curable solvent-free acrylic adhesives that have a variety of excellent performances comparable to solvent-based acrylic adhesives have come to be used. Acrylic syrup (acrylic partial copolymers obtained by partially polymerizing acrylic monomers) can be used as the main component of solvent-free acrylic adhesives.

[0003] In general, acrylic pressure-sensitive adhesives are excellent in adhesive properties such as tackiness, repulsion resistance, and retention (cohesive strength), and in aging resistance such as transparency, heat resistance, light resistance, weather resistance, and oil resistance, etc. Therefore, acrylic pressure-sensitive adhesives have highly reliable adhesive properties for various adherends in a wide range of fields.

[0004] However, acrylic adhesives do not have sufficient adhesion to adherends with low surface free energy (low polarity), such as polyolefin resins such as polyethylene and polypropylene, which are widely used in home appliances, building materials, and automotive interior and exterior materials.

[0005] Polyolefin resins are used in a variety of products because they have heat resistance, high strength, chemical resistance, and versatility. However, they have a problem in that it is difficult to improve the adhesion of acrylic pressure-sensitive adhesives to polyolefin resins because of their low surface free energy.

[0006] In consideration of the above problems, Patent Documents 1 to 3 propose a method of blending a tackifier resin (e.g., a rosin-based resin or a petroleum-based resin) with an acrylic adhesive in order to increase the adhesion of the acrylic adhesive to a low-polarity adherend. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 6-207151 [Patent Document 2] Special Publication No. 11-504054 [Patent Document 3] JP 2003-165958 A Summary of the Invention [Problem to be solved by the invention]

[0008] However, the solvent-based acrylic adhesive of Patent Document 1 uses a large amount of organic solvent, which adversely affects the human body of the worker, and it is necessary to remove unnecessary organic solvent when processing into an adhesive tape, so it is difficult to say that it is environmentally friendly. Furthermore, when a tackifier resin is added to an acrylic syrup (an acrylic partial copolymer obtained by partially polymerizing an acrylic monomer) as proposed in Patent Documents 1 to 3, curing inhibition cannot be sufficiently avoided and sufficient adhesive properties cannot be obtained.

[0009] Therefore, an object of the present invention is to provide a solventless acrylic pressure-sensitive adhesive composition that realizes a pressure-sensitive adhesive sheet having excellent transparency and sufficient adhesive properties to adherends with low polarity. [Means for solving the problem]

[0010] In order to achieve the object of the present invention, the solventless acrylic pressure-sensitive adhesive composition of the present invention comprises either a first acrylic partial copolymer containing 60 to 93 parts by mass of a (meth)acrylic acid ester having an alkyl group with 8 or more carbon atoms, 0 to 30 parts by mass of a (meth)acrylic acid ester having an alkyl group with less than 8 carbon atoms, and 7 to 20 parts by mass of a monomer having a functional group, or a second acrylic partial copolymer containing 0 to 63 parts by mass of a (meth)acrylic acid ester having an alkyl group with 8 or more carbon atoms, 30 to 93 parts by mass of a (meth)acrylic acid ester having an alkyl group with less than 8 carbon atoms, and 7 to 20 parts by mass of a monomer having a functional group, a polyfunctional monomer, and a tackifier resin, wherein the tackifier resin is a hydrogenated petroleum resin, and the tackifier resin is contained in an amount of 0.5 to 4.5 parts by mass per 100 parts by mass of the second acrylic partial copolymer. Effect of the Invention

[0011] According to the present invention, it is possible to provide a solventless acrylic pressure-sensitive adhesive composition that realizes a pressure-sensitive adhesive sheet having excellent transparency and sufficient adhesive properties to adherends with low polarity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The following embodiments are described in detail. Note that the following embodiments do not limit the scope of the invention, and not all of the combinations of features described in the embodiments are essential to the invention. Two or more of the features described in the embodiments may be combined in any combination.

[0013] In this specification, the numerical range specified by using "~" includes the numerical values ​​before and after "~" as the lower and upper limit ranges. In this specification, "parts" refers to "parts by mass" as the unit of the amount of raw materials blended.

[0014] As used herein, the term "(meth)acrylic" refers to both "acrylic" and "methacrylic," and the term "(meth)acrylate" refers to both "acrylate" and "methacrylate." As used herein, "adhesive properties" refers to the properties relating to adhesive strength, holding power, and constant-load peel strength of an adhesive sheet, which are measured in Tests 1 to 3 described below. "Transparency of an adhesive sheet" refers to the qualitative transparency of the adhesive layer under visible light (e.g., wavelengths of 380 to 780 nm) conditions, which is evaluated in Test 4 described below.

[0015] <Solvent-free acrylic adhesive composition> The solvent-free acrylic pressure-sensitive adhesive composition contains either a first acrylic partial copolymer or a second acrylic partial copolymer, a polyfunctional monomer, and a tackifier resin. Note that the solvent-free acrylic pressure-sensitive adhesive composition contains either a first acrylic partial copolymer or a second acrylic partial copolymer, but is not limited thereto, and may contain the first acrylic partial copolymer and the second acrylic partial copolymer in any blending ratio.

[0016] The solvent-free acrylic pressure-sensitive adhesive composition does not substantially contain a solvent. "Substantially not containing a solvent (e.g., an organic solvent)" means that an organic solvent is not actively blended into the solvent-free acrylic pressure-sensitive adhesive composition, except in cases where the organic solvent is inevitably mixed in. The solvent content of the solvent-free acrylic pressure-sensitive adhesive composition is preferably 2% by weight or less, more preferably 0 to 2% by weight, and even more preferably 0 to 1% by weight, based on 100% by weight of the solvent-free acrylic pressure-sensitive adhesive composition. If the solvent content is too high, air bubbles may be generated in the pressure-sensitive adhesive layer, and the durability of the pressure-sensitive adhesive sheet may decrease.

[0017] <First acrylic partial copolymer and second acrylic partial copolymer> The first acrylic partial copolymer and the second acrylic partial copolymer are copolymers obtained by partially copolymerizing acrylic monomers, and are also referred to as "acrylic syrup" in this specification. The advantages of the solventless acrylic pressure-sensitive adhesive composition containing acrylic syrup are as follows. For example, since it is not necessary to remove the solvent or promote crosslinking after application of the acrylic pressure-sensitive adhesive composition, a pressure-sensitive adhesive sheet can be obtained through a work process that is environmentally friendly and highly safe for the human body.

[0018] The first acrylic partial copolymer contains 60 to 93 parts by mass of a (meth)acrylic acid ester having an alkyl group with 8 or more carbon atoms, 0 to 30 parts by mass of a (meth)acrylic acid ester having an alkyl group with less than 8 carbon atoms, and 7 to 20 parts by mass of a monomer having a functional group. Here, the content of the (meth)acrylic acid ester having an alkyl group with 8 or more carbon atoms is preferably 60 to 93 parts by mass, 60 to 90 parts by mass, or 65 to 90 parts by mass. The content of the (meth)acrylic acid ester having an alkyl group with less than 8 carbon atoms is preferably 0 to 30 parts by mass, 0 to 28 parts by mass, or 0 to 25 parts by mass. The content of the monomer having a functional group is preferably 7 to 20 parts by mass, 7 to 15 parts by mass, or 10 to 15 parts by mass. The first acrylic partial copolymer may further contain other monomers copolymerizable with the above monomers.

[0019] The second acrylic partial copolymer contains 0 to 63 parts by mass of a (meth)acrylic acid ester having an alkyl group with 8 or more carbon atoms, 30 to 93 parts by mass of a (meth)acrylic acid ester having an alkyl group with less than 8 carbon atoms, and 7 to 20 parts by mass of a monomer having a functional group. Here, the content of the (meth)acrylic acid ester having an alkyl group with 8 or more carbon atoms is preferably 0 to 63 parts by mass, 0 to 60 parts by mass, or 0 to 55 parts by mass. The content of the (meth)acrylic acid ester having an alkyl group with less than 8 carbon atoms is preferably 30 to 93 parts by mass, 33 to 93 parts by mass, or 35 to 90 parts by mass. The content of the monomer having a functional group is preferably 7 to 20 parts by mass, 7 to 15 parts by mass, or 10 to 15 parts by mass. The second acrylic partial copolymer may further contain other monomers copolymerizable with the above monomers.

[0020] ((Meth)acrylic acid ester) (Meth)acrylic acid esters are classified into (meth)acrylic acid esters in which the alkyl group has 8 or more carbon atoms and (meth)acrylic acid esters in which the alkyl group has less than 8 carbon atoms.

[0021] Examples of (meth)acrylic acid esters having an alkyl group with 8 or more carbon atoms include normal octyl (meth)acrylate, isooctyl (meth)acrylate, 2-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, normal nonyl (meth)acrylate, isononyl (meth)acrylate, normal decyl (meth)acrylate, isodecyl (meth)acrylate, and lauryl (meth)acrylate. These monomers may be used alone or in combination of two or more.

[0022] Examples of (meth)acrylic acid esters having an alkyl group with less than 8 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, and heptyl (meth)acrylate. These monomers may be used alone or in combination of two or more.

[0023] (Monomers with functional groups) The monomer having a functional group includes at least one of a monomer having a hydroxy group, a monomer having a carboxy group, and a monomer having an amide group.

[0024] Examples of monomers having a hydroxy group include (meth)acrylic acid esters (hydroxyalkyl (meth)acrylates) having a hydroxy group, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. These monomers may be used alone or in combination of two or more.

[0025] Examples of the monomer having a carboxy group include (meth)acrylic acid esters having a carboxy group such as 2-carboxyethyl (meth)acrylate; and unsaturated carboxylic acids such as (meth)acrylic acid, crotonic acid, maleic acid, itaconic acid, fumaric acid, citraconic acid, and mesaconic acid. These monomers are used alone or in combination of two or more. In particular, acrylic acid is preferred as the monomer having a carboxy group from the viewpoint of improving the cohesive strength of the solventless acrylic pressure-sensitive adhesive composition and the pressure-sensitive adhesive layer.

[0026] Examples of the monomer having an amide group include (meth)acrylamide, isopropyl(meth)acrylamide, dimethylaminopropyl(meth)acrylamide, and hydroxyethyl(meth)acrylamide. These monomers may be used alone or in combination of two or more.

[0027] (Other Monomers) Examples of other monomers include styrene, vinyl acetate, and (meth)acrylonitrile. These monomers may be used alone or in combination of two or more.

[0028] (Polymerization method) The first acrylic partial copolymer and the second acrylic partial copolymer can be produced by ordinary solution polymerization, bulk polymerization, polymerization by active energy ray irradiation, etc., but bulk polymerization and active energy ray polymerization that do not use a solvent are preferred. By bulk polymerization and active energy ray polymerization, the first acrylic partial copolymer and the second acrylic partial copolymer can be obtained without going through a process such as desolvation, and can be used as is in the production of the solventless acrylic pressure-sensitive adhesive composition of the present invention.

[0029] (Thermal polymerization initiator) Examples of the thermal polymerization initiator used in producing the first acrylic partial copolymer and the second acrylic partial copolymer include oil-soluble organic peroxides such as 2,4-dichlorobenzoyl peroxide, t-butyl peroxypivalate, dibenzoyl peroxide, bis(2-methylbenzoyl) peroxide, bis(3,5,5-trimethylhexanoyl) peroxide, dioctanoyl peroxide, t-butylperoxy-2-ethylhexanoate, cyclohexanone peroxide, methyl ethyl ketone peroxide, dicumyl peroxide, dilauroyl peroxide, diisopropylbenzene hydroperoxide, t-butyl hydroperoxide, and di-t-butyl peroxide; and oil-soluble azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), and 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile). These may be used alone or in combination of two or more.

[0030] (Photopolymerization initiator) Examples of photopolymerization initiators used in producing the first acrylic partial copolymer and the second acrylic partial copolymer by irradiation with active energy rays (e.g., ultraviolet light, visible light, infrared light, etc.) include acetophenone-based initiators, benzoin-based initiators, α-hydroxyacetophenone-based initiators, thioxanthone-based initiators, α-aminoacetophenone-based initiators, and acylphosphine oxide-based initiators. These may be used alone or in combination of two or more.

[0031] (Chain transfer agent) In order to adjust the molecular weight of the first acrylic partial copolymer and the second acrylic partial copolymer, a chain transfer agent can be appropriately used. Examples of the chain transfer agent include mercaptans such as octyl thioglycolate, methoxybutyl thioglycolate, octyl mercaptopropionate, methoxybutyl mercaptopropionate, stearyl mercaptan, lauryl mercaptan, and α-methylstyrene dimer. These can be used alone or in a mixture of two or more kinds.

[0032] <Polyfunctional Monomer> The polyfunctional monomer is a monomer containing two or more ethylenically unsaturated groups in one molecule. Examples of the polyfunctional monomer include bisphenol F type EO modified di(meth)acrylate, bisphenol A type EO modified di(meth)acrylate, ethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, polybutylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, di(meth)acrylic acid, and the like. Examples of the (meth)acrylic acid esters of polyhydric alcohols include tetraethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate; and others include vinyl (meth)acrylate and dimethyloltricyclodecane di(meth)acrylate. These polyfunctional monomers can be used alone or in combination of two or more.

[0033] Commercially available polyfunctional monomers include, for example, bisphenol F type EO-modified (n≒2) diacrylate (Aronix M-208 / manufactured by Toagosei Co., Ltd.), trimethylolpropane triacrylate (Aronix M-309 / manufactured by Toagosei Co., Ltd.), and dipentaerythritol penta- and hexaacrylate (Aronix M-400 / manufactured by Toagosei Co., Ltd.).

[0034] The solventless acrylic pressure-sensitive adhesive composition contains 0.1 to 1.5 parts by mass, preferably 0.1 to 1.3 parts by mass, and more preferably 0.1 to 1.0 part by mass of a polyfunctional monomer per 100 parts by mass of each of the first acrylic partial copolymer and the second acrylic partial copolymer.

[0035] <Tackifier resin> The tackifier resin is a thermoplastic resin that has a low molecular weight compared to the main component (acrylic syrup) and is liquid or solid at room temperature. By adding a colorless and transparent tackifier resin to acrylic syrup, a pressure-sensitive adhesive sheet with good transparency and adhesive properties to low-polarity adherends (e.g., olefin-based resins) can be realized. The tackifier resin is preferably, for example, a hydrogenated petroleum resin, which has extremely few double bonds that are a major factor in inhibiting the hardening of acrylic syrup. Hydrogenated petroleum resin is a hydrocarbon resin that is colorless and transparent, has excellent weather resistance and heat resistance, and has almost no odor.

[0036] Examples of hydrogenated petroleum resins include resins obtained by partially or completely hydrogenating aliphatic petroleum resins (C5 petroleum resins), alicyclic petroleum resins (dicyclopentadiene (DCPD) petroleum resins), aromatic petroleum resins (C9 petroleum resins), aliphatic / aromatic copolymer petroleum resins, alicyclic / aromatic copolymer petroleum resins, and aliphatic / alicyclic copolymer petroleum resins. These may be used alone or in combination of two or more. From the viewpoint of improving the transparency and adhesive properties of the pressure-sensitive adhesive sheet, the hydrogenated petroleum resin is preferably a hydrogenated alicyclic petroleum resin or a hydrogenated DCPD petroleum resin.

[0037] From the viewpoint of obtaining good compatibility with the main component (acrylic syrup), the weight average molecular weight (Mw) of the tackifier resin (hydrogenated petroleum resin) is preferably 300 to 2500, more preferably 350 to 2200. Here, the weight average molecular weight (Mw) is a value measured by gel permeation chromatography (GPC) method (value converted into standard polystyrene).

[0038] The softening point of the tackifier resin (hydrogenated petroleum resin) is preferably 80 to 160° C., more preferably 80 to 150° C. By adding a hydrogenated petroleum resin having a softening point within the above range to an acrylic syrup, the cohesive strength of the solventless acrylic pressure-sensitive adhesive composition and the pressure-sensitive adhesive layer thereof can be further improved. The softening point is a value measured by the ring and ball method.

[0039] From the viewpoint of enhancing the transparency of the PSA sheet, the color tone (Hazen unit color number) of the tackifier resin (hydrogenated petroleum resin) is preferably 150 or less, 140 or less, 130 or less, 120 or less, or 110 or less, more preferably 100 or less. Here, the color tone is a value measured in accordance with JIS K0071. The Hazen unit color number is a scale for evaluating the coloration degree of a chemical product that is liquid at room temperature or a chemical product that is heated to a molten state.

[0040] Examples of aliphatic petroleum resins include C5 petroleum resins obtained from C5 petroleum fractions of naphtha. Examples of C5 petroleum fractions include conjugated diolefinic unsaturated hydrocarbons having 4 to 6 carbon atoms, such as isoprene, trans-1,3-pentadiene, cis-1,3-pentadiene, cyclopentadiene, and methylcyclopentadiene; monoolefinic unsaturated hydrocarbons having 4 to 6 carbon atoms, such as butene, 2-methyl-1-butene, 2-methyl-2-butene, 1-pentene, 2-pentene, and cyclopentene; aliphatic saturated hydrocarbons, such as cyclopentane, 2-methylpentane, 3-methylpentane, and n-hexane; and mixtures thereof.

[0041] Examples of alicyclic petroleum resins include dicyclopentadiene (DCPD) petroleum resins obtained from dicyclopentadiene petroleum fractions of naphtha. Examples of dicyclopentadiene petroleum fractions include cyclic aliphatic compounds having 10 carbon atoms such as dicyclopentadiene, cyclic aliphatic compounds having 11 carbon atoms such as methyldicyclopentadiene, cyclic aliphatic compounds having 12 carbon atoms such as dimethyldicyclopentadiene, and mixtures thereof.

[0042] Commercially available hydrogenated alicyclic petroleum resins include: Alcon M-135 (softening point 135°C, manufactured by Arakawa Chemical Industries, Ltd.), Alcon M-115 (softening point 115°C, manufactured by Arakawa Chemical Industries, Ltd.), Alcon M-100 (softening point 100°C, manufactured by Arakawa Chemical Industries, Ltd.), Alcon M-90 (softening point 90°C, manufactured by Arakawa Chemical Industries, Ltd.), Alcon P-140 (fully hydrogenated, softening point 140°C, manufactured by Arakawa Chemical Industries, Ltd.) Alcon P-125 (fully hydrogenated, softening point 125°C, manufactured by Arakawa Chemical Industries, Ltd.) Alcon P-115 (fully hydrogenated, softening point 115°C, manufactured by Arakawa Chemical Industries, Ltd.) Alcon P-100 (fully hydrogenated, softening point 100°C, manufactured by Arakawa Chemical Industries, Ltd.) Alcon P-90 (fully hydrogenated, softening point 90°C, manufactured by Arakawa Chemical Industries, Ltd.) T-REZ HA085 (softening point 88.0℃, manufactured by ENEOS Co., Ltd.), T-REZ HA103 (softening point 104.0℃, manufactured by ENEOS Co., Ltd.), T-REZ HA105 (softening point 105.0℃, manufactured by ENEOS Co., Ltd.), T-REZ HA125 (softening point 125.0° C., manufactured by ENEOS Corp.) can be mentioned. These can be used alone or in combination of two or more kinds.

[0043] Examples of aromatic petroleum resins include C9 petroleum resins obtained from C9 petroleum fractions of naphtha, copolymers obtained by polymerizing C9 petroleum resins alone or in combination, etc. Examples of C9 petroleum fractions include aromatic compounds having 8 carbon atoms such as styrene, aromatic compounds having 9 carbon atoms such as α-methylstyrene, β-methylstyrene, vinyltoluene, and indene, aromatic compounds having 10 carbon atoms such as 1-methylindene, 2-methylindene, and 3-methylindene, aromatic compounds having 11 carbon atoms such as 2,3-dimethylindene and 2,5-dimethylindene, and mixtures thereof.

[0044] The solventless acrylic pressure-sensitive adhesive composition contains 0.5 to 20 parts by mass, preferably 1 to 18 parts by mass, more preferably 1.5 to 16 parts by mass, and even more preferably 1.5 to 15 parts by mass or 2.5 to 15 parts by mass of a tackifier resin relative to 100 parts by mass of the first acrylic partial copolymer. If the solventless acrylic pressure-sensitive adhesive composition does not contain the above-mentioned predetermined amount of a tackifier resin, the adhesive properties of the pressure-sensitive adhesive sheet cannot be improved.

[0045] From the viewpoint of improving the transparency and adhesive properties of the adhesive sheet, the solventless acrylic adhesive composition contains 0.5 to 4.5 parts by mass, preferably 1 to 4.5 parts by mass, more preferably 1.5 to 4.5 parts by mass, and even more preferably 1.5 to 4 parts by mass or 2.5 to 4 parts by mass of a tackifier resin per 100 parts by mass of the second acrylic partial copolymer. On the other hand, if the solventless acrylic adhesive composition contains more than 4.5 parts by mass of a tackifier resin per 100 parts by mass of the second acrylic partial copolymer, the transparency of the adhesive sheet decreases.

[0046] <Photopolymerization initiator> The photopolymerization initiator refers to an initiator capable of generating active species such as radicals by irradiation with active energy rays (e.g., ultraviolet light, visible light, infrared light, etc.), and is, for example, a self-cleavage type photoradical polymerization initiator. Examples of the photopolymerization initiator include acetophenone-based initiators, benzoin-based initiators, α-hydroxyacetophenone-based initiators, thioxanthone-based initiators, α-aminoacetophenone-based initiators, and acylphosphine oxide-based initiators. These are used alone or in combination of two or more. From the viewpoint of discoloration of the polymerized product, the photopolymerization initiator is preferably a self-cleavage type photoradical polymerization initiator.

[0047] The advantages of the solvent-free acrylic adhesive composition containing a photopolymerization initiator and curing with ultraviolet light are as follows. For example, no curing is required after application of the solvent-free acrylic adhesive composition, and an adhesive sheet can be obtained in a short process and time. In this way, it is possible to contribute to improving the production efficiency of adhesive sheets and reducing manufacturing costs.

[0048] Examples of the acetophenone-based initiator include acetophenone, 2,2-diethoxyacetophenone, benzyl dimethyl ketal, and hydroxyacetophenone. These may be used alone or in combination of two or more.

[0049] Examples of the benzoin initiator include benzoin, benzoin methyl ether, and benzoin isopropyl ether. These may be used alone or in combination of two or more.

[0050] Examples of α-hydroxyacetophenone initiators include 1-hydroxycyclohexyl phenyl ketone and 2-hydroxy-2-methyl-1-phenyl-1-propanone. These are used alone or in combination of two or more. Examples of commercially available α-hydroxyacetophenone initiators include Omnirad184 (manufactured by IGM Resins).

[0051] Examples of thioxanthone initiators include 2-isopropylthioxanthone, 2,4-dimethylthioxanthone, and 2,4-diethylthioxanthone. These may be used alone or in combination of two or more.

[0052] Examples of the α-aminoacetophenone initiator include 2-methyl-[4-(methylthio)phenyl]-2-morpholino-1-propanone and 2-benzyl-2-(dimethylamino)-1-[4-(morpholino)phenyl]-1-butanone, which may be used alone or in combination of two or more.

[0053] Examples of the acylphosphine oxide initiator include phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide. These are used alone or in combination of two or more. Examples of commercially available acylphosphine oxide initiators include OmniradTPO H (manufactured by IGM Resins).

[0054] The solventless acrylic pressure-sensitive adhesive composition contains 0.1 to 1.5 parts by mass, preferably 0.3 to 1.2 parts by mass, of a photopolymerization initiator per 100 parts by mass of the first acrylic partial copolymer and the second acrylic partial copolymer.

[0055] <Other additives> The solventless acrylic adhesive composition may contain various additives as necessary within the range that does not inhibit the adhesive performance of the adhesive sheet. Examples of other additives include antioxidants, ultraviolet absorbers, fillers, pigments, thickeners, antistatic agents, silane coupling agents, and flame retardants. These are used alone or in combination of two or more.

[0056] <Adhesive> The solvent-free acrylic adhesive composition of the present invention is cured by irradiation with active energy rays (e.g., ultraviolet rays), so that thick coating is possible. In addition, the adhesive using the solvent-free acrylic adhesive composition can be suitably used as an adhesive for double-sided adhesive applications, impact resistance applications, and strong adhesive applications. Examples of the adherend to which the adhesive of the present invention is applied include glass, ITO transparent electrode sheets, low polarity materials such as polyolefin resins, optical sheets such as polyethylene terephthalate (PET), polycarbonate (PC), and polymethyl methacrylate (PMMA), and optical members such as polarizing plates, retardation plates, optical compensation films, and brightness enhancement films. Furthermore, since the adhesive of the present invention has excellent transparency, it can be suitably used for display devices including at least any of the above optical members. In addition, the adhesive of the present invention can be used as an adhesive for various labels and adhesive for masking.

[0057] <Adhesive sheet> The pressure-sensitive adhesive sheet of the present invention comprises a substrate and a pressure-sensitive adhesive layer made of the solvent-free acrylic pressure-sensitive adhesive composition of the present invention provided on at least one surface of the substrate. The pressure-sensitive adhesive layer is formed by curing the solvent-free acrylic pressure-sensitive adhesive composition using active energy rays. The pressure-sensitive adhesive sheet of the present invention can be used in combination with the pressure-sensitive adhesive described above, and can be used for the same purpose as the pressure-sensitive adhesive. The pressure-sensitive adhesive layer and the pressure-sensitive adhesive sheet can be formed by the method described below.

[0058] The solvent-free acrylic pressure-sensitive adhesive composition of the present invention is applied to a substrate to form a coating film, and if necessary, a cover film for protecting the coating film is laminated on the coating film.

[0059] (Substrate and cover film) Examples of the substrate and cover film include plastic films such as polyester (e.g., polyethylene terephthalate (PET), polyethylene naphthalate), polycarbonate, polymethyl methacrylate, polyethylene, polypropylene, cyclic olefin, polyvinyl chloride, polyurethane, polyamide, and ethylene-vinyl acetate copolymer; inorganic materials such as glass plates; nonwoven fabrics; and paper. The substrate and cover film may have a surface that has been subjected to a release treatment with a release agent such as silicone. The thickness of the substrate and cover film is not particularly limited, but is, for example, 5 to 500 μm.

[0060] (Application method) Examples of a method for coating (applying) the solventless acrylic pressure-sensitive adhesive composition on any surface (one surface or both surfaces) of a substrate include a method using a coater such as a gravure coater, a roll coater, a curtain flow coater, a spin coater, a bar coater, a reverse coater, a die coater, a kiss coater, a fountain coater, a rod coater, an air doctor coater, a knife coater, a blade coater, a cast coater or a screen coater; a method using a sprayer such as an air spray, an airless spray or a rotor dampening; and an immersion method such as dipping.

[0061] (Curing method) When the solvent-free acrylic pressure-sensitive adhesive composition contains a photopolymerization initiator, the coating film can be irradiated with active energy rays to cure the solvent-free acrylic pressure-sensitive adhesive composition. Examples of active energy rays include ultraviolet rays, visible rays, infrared rays, and the like, and ultraviolet rays are particularly preferred. The integrated light amount of the active energy rays is preferably 100 to 7000 mJ / cm. 2 , more preferably 500 to 3000 mJ / cm 2 The illuminance of the active energy rays is preferably 50 to 700 mW / cm. 2 , more preferably 100 to 500 mW / cm 2Examples of the light source include a low pressure mercury lamp, a high pressure mercury lamp, an extra high pressure mercury lamp, a carbon arc lamp, a xenon lamp, a metal halide lamp, a chemical lamp, a black light fluorescent lamp, and an electrodeless UV lamp.

[0062] (Adhesive layer) The thickness of the adhesive layer can be appropriately selected depending on the application, and is, for example, 3 to 1000 μm, preferably 5 to 500 μm, and more preferably 7 to 300 μm, from the viewpoint of imparting sufficient adhesive strength to the adhesive sheet.

[0063] <Method of manufacturing acrylic syrups A to F> Table 1 shows the raw material composition and physical properties of the acrylic syrup. Based on the raw material composition of acrylic syrup A in Table 1, a reaction apparatus equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube was charged with nitrogen gas, and then 90 parts of 2-ethylhexyl acrylate (2EHA), 10 parts of acrylic acid (AAC), and 0.005 parts of a thermal polymerization initiator (2,2'-azobisisobutyronitrile) were charged. While stirring, the mixture was reacted at 63°C for 1 hour in a nitrogen gas stream. After the reaction was completed, the mixture was diluted with monomers of the same composition ratio to obtain acrylic syrup A with an evaporation residue of 8.4% by mass. The viscosity of acrylic syrup A was measured using a viscometer (manufactured by Toki Sangyo Co., Ltd., device name: B-type viscometer).

[0064] Acrylic syrups B to F are based on the raw material composition in Table 1 and are obtained by the same process as acrylic syrup A, so detailed explanation will be omitted.

[0065] <Method of manufacturing solvent-based adhesive A> Based on the raw material composition of the solvent-based pressure-sensitive adhesive A in Table 1, a reactor equipped with a stirrer, a thermometer, a successive dropping device, a reflux condenser, and a nitrogen inlet tube was charged with nitrogen gas, and then 45 parts of ethyl acetate and 0.1 parts of a thermal polymerization initiator (2,2'-azobisisobutyronitrile) were charged. Meanwhile, a monomer mixture consisting of 90 parts of 2-ethylhexyl acrylate (2EHA) and 10 parts of acrylic acid (AAC) was prepared in another container. The above reactor was heated to 90°C in a nitrogen gas stream, and the monomer mixture weighed in another container was dropped over 60 minutes, and a polymerization reaction was carried out at 90°C for 7 hours. After the reaction was completed, the mixture was diluted with ethyl acetate to obtain a solvent-based pressure-sensitive adhesive A of an acrylic polymer with an evaporation residue of 50.0% by mass.

[0066] [Table 1] (remarks) Acrylic syrups A to D: equivalent to the first acrylic partial copolymer Acrylic syrups E to F: equivalent to the second acrylic partial copolymer Monomers with C8 or more: (meth)acrylic acid esters with alkyl groups having 8 or more carbon atoms Monomers with less than C8: (meth)acrylic acid esters with alkyl groups with less than 8 carbon atoms 2EHA: 2-Ethylhexyl acrylate ·BA: Butyl acrylate ·NOAA: Normal octyl acrylate AAC: Acrylic acid

[0067] <Method of producing solventless acrylic pressure-sensitive adhesive composition> Table 2 shows the raw material blends of the solventless acrylic pressure-sensitive adhesive compositions of Examples 1 to 13. Based on the raw material blends of Example 1 in Table 2, 0.4 parts of Aronix M-208 (trade name, manufactured by Toagosei Co., Ltd.) as polyfunctional monomer A, 2.5 parts of Alcon P-100 (trade name, manufactured by Arakawa Chemical Industries Co., Ltd.) as tackifier resin A, and 0.5 parts of Omnirad184 (trade name, manufactured by IGM Resins Co., Ltd.) as photopolymerization initiator A were added to 100 parts of acrylic syrup A and thoroughly mixed to obtain the solventless acrylic pressure-sensitive adhesive composition of Example 1.

[0068] The solventless acrylic pressure-sensitive adhesive compositions of Examples 2 to 13 were obtained using the raw material compositions shown in Table 2 and in the same process as in Example 1.

[0069] Table 3 shows the raw material blends of the solventless / solvent-based acrylic pressure-sensitive adhesive compositions of Comparative Examples 1 to 9. The solventless / solvent-based acrylic pressure-sensitive adhesive compositions of Comparative Examples 1 to 9 were obtained based on the raw material blends in Table 3 and the same process as in Example 1. In the solvent-based acrylic pressure-sensitive adhesive composition of Comparative Example 9, tackifier resin A was not sufficiently dissolved in the solvent-based pressure-sensitive adhesive A, and precipitation of tackifier resin A (hydrogenated petroleum resin) was observed in large amounts. Therefore, it was not possible to prepare an evaluation sample described below using the solvent-based acrylic pressure-sensitive adhesive composition of Comparative Example 9.

[0070] [Table 2] (remarks) Multifunctional monomer A: Bisphenol F type EO modified (n≒2) diacrylate (Aronix M-208 / Toagosei Co., Ltd.) Polyfunctional monomer B: Trimethylolpropane triacrylate (Aronix M-309 / Toagosei Co., Ltd.) Multifunctional monomer C: Dipentaerythritol penta- and hexaacrylate (Aronix M-400 / Toagosei Co., Ltd.) Monofunctional monomer: Phenol EO modified acrylate (Aronix M-101A / Toagosei Co., Ltd.) Tackifier resin A: Hydrogenated petroleum resin (Arcon P-100 / Arakawa Chemical Co., Ltd.) Tackifier resin B: Hydrogenated petroleum resin (Alcon P-125 / Arakawa Chemical Co., Ltd.) ·Tackifying resin C: Hydrogenated petroleum resin (T-REZ HA105 / manufactured by ENEOS) Tackifying resin D: Hydrogenated rosin ester resin (Pine Crystal KE-311 / Arakawa Chemical Co., Ltd.) Tackifying resin E: Hydrogenated rosin ester resin (Pine Crystal KE-359 / Arakawa Chemical Co., Ltd.) Tackifying resin F: Aromatic hydrogenated terpene resin (Clearon K-100 / Yasuhara Chemical Co., Ltd.) Tackifier resin G: Aromatic hydrocarbon resin (FTR-6100 / Mitsui Chemicals) Photopolymerization initiator A: 1-hydroxycyclohexyl phenyl ketone (Omnirad184 / IGM Resins) Photopolymerization initiator B: Diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide (OmniradTPO H / IGM Resins) Hardener: Tolylene diisocyanate (Takenate D-101E (45EA) / Mitsui Chemicals)

[0071] [Table 3] (remarks) The explanation is the same as in Table 2, so it is omitted.

[0072] <Creating evaluation samples> The solventless acrylic pressure-sensitive adhesive compositions of Examples 1 to 13 and Comparative Examples 1 to 8 were used to prepare the following evaluation samples.

[0073] Using each of the solventless acrylic pressure-sensitive adhesive compositions of Examples 1 to 13 and Comparative Examples 1 to 8, a 35 μm thick pressure-sensitive adhesive layer was formed on a PET film by the following method to prepare a pressure-sensitive adhesive sheet. Each solventless acrylic pressure-sensitive adhesive composition was applied onto a silicone resin-coated PET film (releasable substrate), and then the PET film was laminated and cured by irradiating with ultraviolet light under the following ultraviolet curing conditions. The ultraviolet curing conditions were: illuminance 300 mW / cm2 using a metal halide lamp, cumulative light quantity 1550 mJ / cm 2 The irradiation conditions at 1000 ℃ were included. The UV POWER PUCK manufactured by EIT was used as the illuminance and light intensity meter.

[0074] <Evaluation of adhesive properties and transparency> Tests 1 to 4 were carried out using each of the evaluation samples (adhesive sheets) thus produced, and the adhesive properties and transparency were evaluated.

[0075] (Test 1: Measurement of adhesive strength) For each adhesive sheet, the 180° peel adhesive strength against a test plate (polypropylene (PP) plate) was measured in an environment of 23°C and 50% RH according to JIS Z0237. Specifically, the adhesive sheet was cut to a width of 25 mm, attached to a polypropylene (PP) plate, and pressed once back and forth with a pressing roll under a load of 2 kg to prepare a test piece for measuring the adhesive strength against the PP plate. After being pressed and left at 23°C for 20 minutes, the adhesive sheet was peeled off from the test piece at a peel speed of 300 mm / min, and the adhesive strength against the PP plate was measured. The adhesive strength of the adhesive sheet was evaluated based on the following evaluation criteria. (Evaluation Criteria) Pass: Adhesive strength is 5.0N / 25mm or more Fail: Adhesive strength is less than 5.0N / 25mm

[0076] (Test 2: Measurement of holding power) Each adhesive sheet was cut to a size of 25 mm wide and 50 mm long to prepare a test piece for measuring the holding power. This test piece was attached to a polypropylene (PP) plate so that the adhesive area was 25 mm x 25 mm according to JIS Z0237, and pressed once with a pressure roller under a load of 2 kg. After that, it was left in an environment of 23 ° C and 50% RH for 60 minutes, and then a weight of 0.5 kg was attached including a hook for attaching the weight in an environment of 80 ° C., and the distance of the test piece that had shifted after 60 minutes (shift length; mm) or the time it took for the test piece to completely peel off (fall time; minutes) was measured. The holding power of the adhesive sheet was evaluated based on the following evaluation criteria. (Evaluation Criteria) Pass: The deviation length is 1.0 mm or less Fail: The slippage exceeds 1.0 mm or the test piece falls within 60 minutes of holding time.

[0077] (Test 3: Measurement of constant load peel strength) Each adhesive sheet was cut to a size of 25 mm wide and 70 mm long to prepare a test piece for measuring the constant load peeling force. The test piece was attached to a polypropylene (PP) plate so that the adhesive area was 25 mm x 50 mm, and was pressed back and forth once with a pressure roller under a load of 2 kg. After that, it was left in an environment of 23 ° C and 50% RH for 60 minutes, and then in an environment of 40 ° C, the pressed tape sample was set in a dedicated jig, and a weight of 0.05 kg was attached to the end of the tape sample to be evaluated, including a hook for attaching the weight, so that a load for peeling in a 90 ° direction relative to the adhesive surface was applied. The peeling distance (peel length; mm) of the test piece after 60 minutes, or the time when the test piece completely peeled off (fall time; minutes) was measured. The constant load peeling force of the adhesive sheet was evaluated based on the following evaluation criteria. (Evaluation Criteria) Pass: Peel length is 20.0 mm or less Fail: The peel length exceeds 20.0 mm or the test piece falls within 60 minutes of holding time.

[0078] (Test 4: Transparency) The transparency of the pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet was visually confirmed under visible light, and the transparency of the pressure-sensitive adhesive sheet was evaluated based on the following evaluation criteria. (Evaluation Criteria) Pass: The adhesive layer is transparent (marked as ◯ in Tables 2-3) Failed: The adhesive layer is whitened (marked as × in Tables 2 to 3)

[0079] <Test Results> Table 2 shows the test results of Examples 1 to 13. Table 3 shows the test results of Comparative Examples 1 to 9. Examples 1 to 13 had good adhesive properties (adhesive strength, holding strength, constant load peel strength) in a well-balanced manner against a low-polarity adherend (polypropylene (PP)), and had good transparency. On the other hand, Comparative Examples 1 to 8 did not have good adhesive properties in a well-balanced manner against a low-polarity adherend (polypropylene (PP)). In particular, Comparative Example 8 showed excellent adhesive properties, but showed whitening of the adhesive layer. Note that for Comparative Example 9, tackifier resin A (hydrogenated petroleum resin) was not dissolved in solvent-based adhesive A, and an evaluation sample (adhesive sheet) could not be prepared, so Tests 1 to 4 were not performed.

[0080] The characteristics of Comparative Examples 1 to 9 are described below. Comparative Example 1 shows a solventless acrylic pressure-sensitive adhesive composition that does not contain a tackifier resin. Comparative Example 2 shows a solventless acrylic pressure-sensitive adhesive composition that contains a monofunctional monomer instead of a polyfunctional monomer. Comparative Examples 3 and 4 show solventless acrylic pressure-sensitive adhesive compositions that contain a hydrogenated rosin ester resin. Comparative Examples 5 and 6 show solventless acrylic pressure-sensitive adhesive compositions that contain an aromatic hydrogenated terpene resin. Comparative Example 7 shows a solventless acrylic pressure-sensitive adhesive composition that contains an aromatic hydrocarbon resin. Comparative Example 8 shows a solventless acrylic pressure-sensitive adhesive composition that contains a hydrogenated petroleum resin in an amount greater than the amount specified in the present invention relative to the second acrylic partial copolymer. Comparative Example 9 shows a solvent-based acrylic pressure-sensitive adhesive composition.

[0081] According to the test results in Tables 2 and 3, it is presumed that by using a solventless acrylic pressure-sensitive adhesive composition containing at least a hydrogenated petroleum resin and a polyfunctional monomer as a tackifier resin, a pressure-sensitive adhesive sheet having excellent transparency and sufficient adhesive properties to low-polarity adherends can be realized.

[0082] As described above, the solventless acrylic pressure-sensitive adhesive composition of the present invention has a remarkable effect of realizing a pressure-sensitive adhesive sheet having excellent transparency and sufficient adhesive properties to adherends with low polarity.

[0083] Furthermore, the present invention can provide a solvent-free acrylic pressure-sensitive adhesive composition that is environmentally friendly and highly safe for the human body, making it possible to contribute to the achievement of Goal 12 of the Sustainable Development Goals (SDGs) led by the United Nations, "Responsible Consumption and Production."

[0084] The invention is not limited to the above-described embodiment, and various modifications and variations are possible within the scope of the gist of the invention.

Claims

1. either a first acrylic partial copolymer containing 60 to 93 parts by mass of a (meth)acrylic acid ester having an alkyl group with 8 or more carbon atoms, 0 to 30 parts by mass of a (meth)acrylic acid ester having an alkyl group with less than 8 carbon atoms, and 7 to 20 parts by mass of a monomer having a functional group, or a second acrylic partial copolymer containing 0 to 63 parts by mass of a (meth)acrylic acid ester having an alkyl group with 8 or more carbon atoms, 30 to 93 parts by mass of a (meth)acrylic acid ester having an alkyl group with less than 8 carbon atoms, and 7 to 20 parts by mass of a monomer having a functional group; A multifunctional monomer, a tackifying resin; The tackifier resin is a hydrogenated petroleum resin, The tackifier resin is contained in an amount of 0.5 to 4.5 parts by mass relative to 100 parts by mass of the second acrylic partial copolymer. A solvent-free acrylic pressure-sensitive adhesive composition.

2. The tackifier resin is contained in an amount of 0.5 to 20 parts by mass relative to 100 parts by mass of the first acrylic partial copolymer. The solventless acrylic pressure-sensitive adhesive composition according to claim 1 .

3. The tackifier resin is contained in an amount of 1.5 to 15 parts by mass relative to 100 parts by mass of the first acrylic partial copolymer, The tackifier resin is contained in an amount of 1.5 to 4 parts by mass relative to 100 parts by mass of the second acrylic partial copolymer. The solventless acrylic pressure-sensitive adhesive composition according to claim 1 .

4. The tackifier resin is a hydrogenated alicyclic petroleum resin, The solventless acrylic pressure-sensitive adhesive composition according to claim 1 .

5. The tackifier resin is a hydrogenated DCPD-based petroleum resin. The solventless acrylic pressure-sensitive adhesive composition according to claim 1 .

6. The weight average molecular weight (Mw) of the tackifier resin is 300 to 2500, Here, the weight average molecular weight (Mw) is measured by a GPC method. The solventless acrylic pressure-sensitive adhesive composition according to claim 1 .

7. The softening point of the tackifier resin is 80 to 160° C. Here, the softening point is measured by the ring and ball method. The solventless acrylic pressure-sensitive adhesive composition according to claim 1 .

8. The color tone (Hazen color scale) of the tackifier resin is 150 or less, Here, the color tone (Hazen unit color number) is measured in accordance with JIS K0071. The solventless acrylic pressure-sensitive adhesive composition according to claim 1 .

9. The first acrylic partial copolymer and the second acrylic partial copolymer each contain 0.1 to 1.5 parts by mass of the polyfunctional monomer relative to 100 parts by mass of each of the first acrylic partial copolymer and the second acrylic partial copolymer. The solventless acrylic pressure-sensitive adhesive composition according to claim 1 .

10. The first acrylic partial copolymer and the second acrylic partial copolymer each contain 0.1 to 1.0 part by mass of the polyfunctional monomer relative to 100 parts by mass of each of the first acrylic partial copolymer and the second acrylic partial copolymer. The solventless acrylic pressure-sensitive adhesive composition according to claim 1 .

11. Further comprising a photoinitiator, The photopolymerization initiator is contained in an amount of 0.1 to 1.5 parts by mass per 100 parts by mass of each of the first acrylic partial copolymer and the second acrylic partial copolymer. The solventless acrylic pressure-sensitive adhesive composition according to claim 1 .

12. The photopolymerization initiator is a self-cleavage type photoradical polymerization initiator. The solventless acrylic pressure-sensitive adhesive composition according to claim 11.

13. The monomer having a functional group includes at least one of a monomer having a hydroxy group, a monomer having a carboxy group, and a monomer having an amide group. The solventless acrylic pressure-sensitive adhesive composition according to claim 1 .

14. A substrate; and a pressure-sensitive adhesive layer comprising the solventless acrylic pressure-sensitive adhesive composition according to any one of claims 1 to 13 and provided on at least one surface of the substrate. Adhesive sheet.

15. The pressure-sensitive adhesive layer is formed by curing the solvent-free acrylic pressure-sensitive adhesive composition using active energy rays. The pressure-sensitive adhesive sheet according to claim 14.

Citation Information

Patent Citations

  • Acrylic pressure-sensitive adhesive composition an double-coated tape

    JP1994207151A

  • tackifying acrylic adhesive

    JP1999504054A

  • Uv-curable acrylic pressure-sensitive adhesive composition

    JP2003165958A

Cited By

  • Door weather strip

    US12491758B2